Reading Paul with the reformers : reconciling old and new perspectives - Chester, Stephen J. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2017)
In debates surrounding the New Perspective on Paul, the sixteenth-century Protestant Reformers are often characterized as the apostle's misinterpreters in chief. In this book Stephen Chester challenges that conception with a careful and nuanced reading of the Reformers' Pauline exegesis. Examining the overall contours of early Reformation exegesis of Paul, Chester contrasts the Reformers with their Roman opponents and explores particular contributions made by such key figures as Luther, Melanchthon, and Calvin. He relates their insights to contemporary debates in Pauline theology about justification, union with Christ, and other central themes, arguing that their work remains a significant resource today. Being published in the five-hundredth anniversary year of the Protestant Reformation, Reading Paul with the Reformers reclaims a robust, contemporary understanding of how the Reformers really read Paul.
I. Hermeneutics : the sixteenth century and the twenty-first century -- The hermeneutics of reform : Erasmus, Luther, and contemporary theological interpretation of scripture -- II. Shared convictions : the reformers' new Pauline exegetical grammar -- The medieval context of the reformers : Pauline exegesis and soteriology -- The human plight apart from Christ : sin, the law, and the conscience -- Salvation in Christ : the works of the law, grace, and faith -- III. Individual perspectives : Luther, Melanchthon, and Calvin on righteousness in Christ -- Alien righteousness in Christ : the integration of justification by faith and union with Christ in Martin Luther's Pauline exegesis -- Relational righteousness : justification on account of Christ in Philip Melanchthon's Pauline exegesis -- Righteousness and reciprocity : justification and the works of the believer in John Calvin's Pauline exegesis -- IV. Contemporary implications : the reformers and the new perspective on Paul -- Mapping complexity : a revised account of the relationship between reformation exegesis and the "new perspective on Paul" -- Righteousness in Christ : towards the reconciliation of the perspectives.
Includes bibliographical references (pages 431-453) and index.
Keywords: Bible. -- Criticism, interpretation, etc. -- History -- 16th century